Supramolecular organic frameworks with ultralong phosphorescence via breaking π-Conjugated structures. (March 2020) - Yao, Wei; Ma, Chaoqun; Ma, Huili; Fu, Lishun; Lu, Song; Lv, Anqi; Cai, Suzhi; Hang, Xiaochun; Singh, Manjeet; Shi, Huifang; An, Zhongfu; Huang, Wei
Abstract: Development of crystalline porous materials with luminescent properties have gradually attracted attention for their potential applications in drug delivery, bioimaging, photoelectronic and so on. To date, it is a formidable challenge to rationally design porous phosphorescent materials. Herein, we have reported a chemical strategy of breaking π-conjugated structures of phosphorescent molecules by alkyl chain to achieve supramolecular organic framework (SOFs) with visible ultralong phosphorescence (lifetime > 600 ms). The molecules having broken π-conjugation by flexible alkyl chain will be beneficial to produce short-range π-π stacking for forming luminescent SOFs. Effective π-π stacking between chromophores stabilized triplet excitons to contribute to ultra-long phosphorescence. This work demonstrates a new approach to design porus materials with ultralong phosphorescence and will expand the potential applications of organic phosphorescent crystals with diverse pores.